2020
DOI: 10.1123/kr.2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Barrier Self-Efficacy and Physical Activity in Children and Adolescents: A Meta-Analysis

Abstract: Previous reviews have highlighted the importance of self-efficacy beliefs in maintaining adequate levels of childhood physical activity (PA), but variable findings with different age groups and measures of PA indicate the need to quantify the extant literature. The purpose of this meta-analysis was to estimate the relationship between adolescents’ barrier self-efficacy (BSE) and PA behavior using a random-effects model and to examine age and type of PA measurement as potential relationship moderators. A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Although research has identified several psychosocial factors as being associated with adolescents’ PA, the following three have received increased attention due to their relatively consistent positive relationships with the behavior: perceived PA self-efficacy, social support for PA, and motivation for PA. Strategies to enhance these psychosocial factors are encouraged to both increase adolescents’ MVPA and decrease their sedentary screen time behavior (Hill et al, 2019; Huffman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although research has identified several psychosocial factors as being associated with adolescents’ PA, the following three have received increased attention due to their relatively consistent positive relationships with the behavior: perceived PA self-efficacy, social support for PA, and motivation for PA. Strategies to enhance these psychosocial factors are encouraged to both increase adolescents’ MVPA and decrease their sedentary screen time behavior (Hill et al, 2019; Huffman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…PA self-efficacy involves confidence adolescents have in their ability to participate in PA when faced with barriers (Bandura, 1986). PA self-efficacy has been identified as a positive psychosocial correlate with PA among children and adolescents, aged 9–17 years (Hill et al, 2019), and has been shown to predict their future PA (Dishman, Dunn, et al, 2010). Previous experiences with a behavior are identified as the major source for developing behavior-specific self-efficacy (Bandura, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our understanding of other factors and optimal approaches to change AMI patient behaviors toward exercising is still lacking 5 . In addition, there is a need for further studies that focus on barriers and benefits to exercise with attention to measurement technique and developmental differences 10 . There are limited studies examining the prediction of exercise self-efficacy among post-AMI patients, including type of AMI, perceived exercise benefits, perceived exercise barriers, and clinical variables such as diabetes mellitus (DM), hypertension, lipid profile, and smoking cigarettes or Argela (water pipes).…”
mentioning
confidence: 99%
“…5 In addition, there is a need for further studies that focus on barriers and benefits to exercise with attention to measurement technique and developmental differences. 10 There are limited studies examining the prediction of exercise self-efficacy among post-AMI patients, including type of AMI, perceived exercise benefits, perceived exercise barriers, and clinical variables such as diabetes mellitus (DM), hypertension, lipid profile, and smoking cigarettes or Argela (water pipes). Therefore, the authors of this study attempt to identify perceived benefits and barriers to exercise among post-AMI patients and to determine factors that predict self-efficacy level, to help nurses to develop effective programs to improve exercise uptake and adherence among such service users.…”
mentioning
confidence: 99%